Extendable Coffee Table Influenced By Beijing’s CCTV Tower - Nur Fatiha Kasirin,; Abdul Halip, Juliana (Research in Management of Technology and Business, 2021)
Coffee table is one of furniture that can be placed in the living room, a place where communication and interaction occurs between people. Nowadays, an increment of population affects the size and space of housing. Most of small housing resident have crucial time to choose their furniture due to limited space. Therefore, the aim of this study is to design and develop an extendable coffee table. Prior to the design process, the design features were determined from the questionnaire. The questionnaire was distributed to a total of 50 respondents live in small housing area in Skudai, Johor Bahru. Prior to the sketching process, the visual study was done on extendable coffee table and coffee table with castor. Later from the visual research, a thumbnail and ideation, idea development and final design were prepared. Findings of questionnaire stated that the design criteria for extendable coffee table are a rectangle in shape, equipped with castor, minimalist style, open and closed storage, and finished with natural colour. The designs of extendable coffee table are designed in stages based on the criteria obtained and presented in mock-up form. Later a design survey is conducted to obtain the final design to develop into a prototype.  Majority (43%) respondents choose Design 2 as the final designs. During the manufacturing of the prototype, there are minor amendments on the design and material used. At the end of the study, the extendable coffee table influenced by CCTV Tower was successfully fabricated.